2006
DOI: 10.1001/archneur.63.12.1686
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Demographic Predictors of Long-term Disability in Patients With Relapsing-Remitting Multiple Sclerosis

Abstract: To identify clinical and demographic factors associated with long-term disability in patients with relapsing-remitting multiple sclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
144
5
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(160 citation statements)
references
References 30 publications
8
144
5
3
Order By: Relevance
“…Relapses presenting with pyramidal tract and sphincter disorders have a poor long-term prognosis when compared with relapses without involvement of these systems (39,40,41,42).…”
mentioning
confidence: 99%
“…Relapses presenting with pyramidal tract and sphincter disorders have a poor long-term prognosis when compared with relapses without involvement of these systems (39,40,41,42).…”
mentioning
confidence: 99%
“…Findings of the current study suggested that VitD level was significantly related to duration of disease [9]. VitD deficiency in patients with MS may be due to less exposure to sunlight because of their illness rather than a less exposure to sunlight relationship.…”
Section: Discussionmentioning
confidence: 57%
“…Individualizing treatments in this way has the potential to help avoid patients' receiving an unsuitable therapy, leading to potential cost benefits. In terms of clinical markers, current information suggests that higher EDSS or Multiple Sclerosis Functional Composite scores at baseline; 89,90 incomplete recovery from the first neurological attack; 91 shorter time to second attack; 91 sphincter, bladder, or bowel symptoms at disease onset;…”
Section: Perspectives For Managed Care Organizations On the Burden Ofmentioning
confidence: 99%
“…91 cerebellar involvement; 91 increased relapse frequency prior to study enrollment; 91 male sex; 91 and older age 91 are all associated with increased risk of disability progression in patients with RRMS. The imaging markers-"black holes" on magnetic resonance imaging at baseline, 92 baseline or early CNS atrophy, 93,94 and baseline activity with T 2 lesions, active T 2 lesions, and/or gadolinium-enhancing [95][96][97][98] lesions-appear to be associated with disability progression.…”
Section: Perspectives For Managed Care Organizations On the Burden Ofmentioning
confidence: 99%